Factors of Complicated Measles in Children Less Than 5 Years of Age - Swati, Bibi Tayyaba; Bibi, Saima; Bibi, Jaweria; Anees, Aleena; Butt, Alvina (Indus Journal of Bioscience Research, 2025)
Background: Complicated measles remains a significant health concern in children, with various factors contributing to its severity. Identifying the predisposing factors such as malnutrition, non-vaccination, and poor socioeconomic status is critical for improving outcomes, especially in resource-limited areas. Objective: To determine the frequency of factors leading to complicated measles in children less than 5 years of age. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from July 2024 to January 2025 in the Department of Pediatrics at Ayub Teaching Hospital, Abbottabad. Methodology: A total of 194 children, aged 1 month to 5 years, diagnosed with complicated measles, were included in the study. Demographic information, including age, gender, residential status, parental education, and socioeconomic status, was collected. The study assessed malnutrition using WHO growth standards and vaccination status via parental reports. Results: The study included 194 children with a mean age of 3.43 ± 1.46 years and a mean weight of 12.41 ± 4.96 kg. The sample comprised 57.7% males and 42.3% females, with equal representation from rural and urban areas. The study found that 45.9% of children were malnourished, 59.3% were non-vaccinated, and 67.5% had poor socioeconomic status. Conclusion: Our study confirmed malnutrition, lack of vaccination, and poor socioeconomic status as key factors for complicated measles in children, aligning with global research. Targeted interventions in nutrition, vaccination, and healthcare access, especially in rural and underprivileged areas, are crucial to reducing disease burden and complications through effective public health initiatives.